Development and Performance Evaluation of Cellulose Acetate-Bentonite Mixed Matrix Membranes for CO2 Separation - Asif Jamil; Momina Zulfiqar; Usama Arshad; Subhan Mahmood; Tanveer Iqbal; Sikander Rafiq; Muhammad Z. Iqbal (Advances in Polymer Technology)
Membrane science is a state-of-the-art environmentally green technology that ascertains superior advantages over traditional counterparts for CO2 capture and separation. In this research, mixed matrix membranes (MMMs) comprising cellulose acetate (CA) with various loadings of bentonite (Bt) clay were fabricated by adopting the phase-inversion technique for CO2/CH4 and CO2/N2 separation. The developed pristine and MMMs were characterized for morphological, thermal, structural, and mechanical analyses. Several techniques such as scanning electron microscopy, thermogravimetric analysis, Fourier transformed infrared spectroscopy, and nano-indentation investigations revealed the promising effect of Bt clay in MMMs as compared to pristine CA membrane. Nano-indentation test identified that elastic modulus and hardness of the MMM with 1 wt. loading was increased by 64% and 200%, respectively, compared to the pristine membrane. The permeability decreased with the incorporation of Bt clay due to uniform dispersion of filler attributed to enhanced tortuosity for the gas molecules. Nevertheless, an increase in gas separation performance was observed with Bt addition up to 1 wt. loading. The opposite trend prevailed with increasing Bt concentration on the separation performance owing to filler agglomeration and voids creation. The maximum value of ideal selectivity (CO2/CH4) was achieved at 2 bar pressure with 1 wt. % Bt loading, which is 79% higher than the pristine CA membrane. For CO2/N2, the ideal selectivity was 123% higher compared to the pristine membrane with 1 wt. % Bt loading at 4 bar pressure.